Correlation between mental health and caries status in Primary School Students - Ayub I. Anwar (Journal of Dentomaxillofacial Science, 2018)
Objective: This study aims to determine the correlation of mental health and caries status of students in Mulia Bhakti Makassar Primary School.Material and Methods: Analytical observational research with cross-sectional study design. The subject of this research was all the students of Primary School Mulia Bhakti Makassar.Results: The results showed a correlation between mental health and caries status with Pearson correlation test, p = 0.004 (p <0.05) and correlation coefficient, r = 0.266. There is a high index of DMF-T in students whose mental health is not normal.Conclusion: There was a correlation between mental health status and dental caries status of students at Mulia Bhakti Makassar Primary School.